2017
DOI: 10.1111/jcmm.13113
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among LRP1 expression, Pyk2 phosphorylation and MMP‐9 activation in left ventricular remodelling after myocardial infarction

Abstract: Left ventricular (LV) remodelling after myocardial infarction (MI) is a crucial determinant of the clinical course of heart failure. Matrix metalloproteinase (MMP) activation is strongly associated with LV remodelling after MI. Elucidation of plasma membrane receptors related to the activation of specific MMPs is fundamental for treating adverse cardiac remodelling after MI. The aim of current investigation was to explore the potential association between the low‐density lipoprotein receptor‐related protein 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The pathological role of sLRP1 in cardiometabolic disease is unclear. Our group has identified the cellular form of LRP1 as a key receptor for cholesterol accumulation in vascular cells 16 19 and cardiomyocytes 20 22 , and showed that this receptor is strongly upregulated in coronary arteries and myocardium in in vivo models 23 25 and patients 22 , 26 28 exposed to cardiovascular risk factors. LRP1 has also the potential to interact with different ligands involved in inflammation 29 and coagulation 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The pathological role of sLRP1 in cardiometabolic disease is unclear. Our group has identified the cellular form of LRP1 as a key receptor for cholesterol accumulation in vascular cells 16 19 and cardiomyocytes 20 22 , and showed that this receptor is strongly upregulated in coronary arteries and myocardium in in vivo models 23 25 and patients 22 , 26 28 exposed to cardiovascular risk factors. LRP1 has also the potential to interact with different ligands involved in inflammation 29 and coagulation 30 .…”
Section: Discussionmentioning
confidence: 99%
“…LRP1 expression is markedly enhanced during hypoxemia and/or ischemia [51,89,90] under the regulation of the hypoxia-inducible factor-1α (HIF-1α) in cardiomyocytes, as well as in cardiac fibroblasts [89,90,91,92] (Figure 1).…”
Section: The Low-density Lipoprotein (Ldl)-receptor Related-proteinmentioning
confidence: 99%
“…LRP1 was also strongly up-regulated in the myocardial tissue in the animal models of ischemia-reperfusion [51,90,91], as well as in patients with ischemic cardiomyopathy, supporting a role for LRP1 in IRI [51]. However, the specific role of LRP1 as a scavenger/signaling/scaffold receptor in cardiomyocytes has not been investigated until recently [51,90,92,93].…”
Section: The Low-density Lipoprotein (Ldl)-receptor Related-proteinmentioning
confidence: 99%
See 2 more Smart Citations